Perencanaan dan Pengelolaan Keuangan Warga Binaan LAPAS di Masa Pandemi Covid-19 Melalui Penguatan Literasi Keuangan - Bahtiar Effendi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to increase the understanding of correctional inmates through assistance in planning and financial management of correctional inmates during the COVID-19 pandemic through strengthening financial literacy. The method of carrying out the activities is carried out by coordinating and mapping the needs of the 111th KODIM 0510 Military Unity Building a Village (TMMD) activity at the RUTAN class I Tangerang, Focus Group Discussion (FGD) and financial literacy education, as well as post-education assistance carried out. The inmates of the Class I Tangerang prison are dominated by elementary and junior high school graduates, who violate the law because of economic needs. This community service program is a solution to overcome the low financial literacy of inmates during the COVID-19 pandemic. The success of this service program is due to the achievement of the target participants and the achievement of the objectives and material of the activity. People who have good financial literacy are able to make the right decisions in managing their finances to face global challenges based on technological advances.